Implimentasi Sistem Informasi Manajemen Pemesanan Makanan Berbasis Website Studi Kasus Ichiban Ramen Samarinda - Ananda, Rolly Rezki; Sutedjo, Bambang; Setiawan Tri Yulianto, Sufiandi; Triyono, Triyono; Fauziah, Fenty (Jurnal Manajemen Sistem Informasi (JMASIF), 2022)
Website-based ordering information systems at restaurants or restaurants are very little implemented by restaurants and restaurants in Indonesia. Ichiban sushi is a full-service Japanese restaurant with the largest number of outlets in Indonesia, the information system for ordering food at Ichiban Sushi is no longer using the conventional system where currently ordering at Ichiban uses website-based ordering. This study aims to see the ease and constraints felt by consumers in the implementation of a website-based ordering information system implemented by Ichiban Sushi Samarinda. The method used in this study using qualitative methods, research data collection with field observations by observing consumers in Ichiban Sushi Samarinda and consumers around Ichiban Sushi Samarinda. The results of this study indicate that a website-based ordering information system makes the food ordering process easy and fast, especially in the pandemic era when research is carried out, consumers are not worried about contracting the covid virus because they do not exchange restaurant menu books. In addition, restaurants will benefit from the collection of consumer data such as consumer contacts and their favorite menus.